A Concerning Variable in Lazada E-Commerce During the Covid-19 Pandemic is Web Appearance and Product Variety's Impact on Buying Interest with Trust: - Sri Lestari Miyati; Henny Welsa; Putri Dwi Cahyani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to identify: 1) The impact of website appearance on buying attention; 2) The impact of product type on buying attention; 3) The impact of website appearance on belief; 4) The impact of product type on belief, and 5) The impact of confidence on buying attention. All customers who have transacted via Lazada make up the population of this research. Purposive sampling is the technique used in this study to collect examples. One hundred twelve responders who were given an online questionnaire received the information. The Sobel Test is used to analyze the data collected. According to the study, website appearance influences positive and significant buying attention, product type influences negative buying attention, website appearance influences positive and significant belief, product type influences positive and essential belief, and confidence influences positive and significant buying attention. Results of the Sobel test show whether confidence may mediate between the effects of product category and website design on consumer attention.